Izzivi ob prehodu v nove proizvodne strukture - Rihtaršič, Borut (Ventil (Ljubljana), 2007)
In the paper an innovative production as one of the key enablers for achievingan innovating environment for the industrial transformation of European enterprises is discussed. It is based on documents treating the technology platform ManuFuture. In this framework the view of transformation of the existing to new manufacturing structures is given and the proposal for establishing an infrastructural center / network for innovating production as a meeting point for research, development and industrialization of new concepts, methods and tools for innovative production is discussed.
Keywords: inovacije; motivacija; poslovni modeli; proizvodne strukture; proizvodni sistemi